Sosialisasi Pelaksanaan Tugas dan Tanggungjawab PTPS Pada Penyelenggaraan Pemilu Serentak Tahun 2024 di Kelurahan Asuhan Kota Pematangsiantar - Sianipar, Herlina Hotmadinar; Sijabat, Osco Parmonangan (LPPM STIKOM Tunas Bangsa, 2024)
There is a need for supervision to be regulated in such a way as to anticipate the various opportunities for potential election legal problems to occur in the election implementation process. Bawaslu as a supervisory institution for the implementation of elections. At the peak stage of the 2024 election, namely the voting and counting of votes at the TPS, there are Polling Place Supervisors (PTPS), part of the lower level Bawaslu structure, who are the flagship of Bawaslu to make the election a success. PTPS is obliged to understand its duties, obligations and authority in carrying out its duties, because it plays a direct role in the field in the election process as the front guard. The functions of PTPS are: First, PTPS's function during elections at TPS is to supervise voting preparations. Second, all voting activities are supervised by PTPS so that they run smoothly according to the provisions. Third, oversee preparations for vote counting. Finally, supervise the implementation of the vote count until the results of the movement of the vote count from the TPS to the PPK. Based on the phenomena that occurred in the field during the General Election on February 14 2024, the HKBP Nommensen Pematangsiantar university service team disseminated the results of the implementation of PTPS duties and responsibilities in the Asuhan sub-district, Pematangsiantar City to the entire community and residents of the Asuhan sub-district, resulting in an open insight in the Asuhan sub-district community, as many as 83% understood. implementation of simultaneous regional elections that occurred in Indonesia, especially in the city of Pematangsiantar.